Impacts of low temperature preservation on mitochondrial DNA copy number in oocytes of the hard coral Echinopora sp. (3rd July 2016) - Tsai, Sujune; Thongpooe, Preeyanuch; Kuo, Fu-Wen; Lin, Chiahsin
Abstract: Given the current threats to coral reefs worldwide, there is an urgent need to develop protocols for the cryopreservation of reef-building corals. However, chilling may alter coral mitochondrial distribution and membrane potential, resulting in reduced ATP production. The aim of this study was to investigate the impacts of chilling on mitochondrial DNA copy number (CN) in oocytes of the hard coral Echinopora sp. Oocytes were exposed to 0.5 M, 1 M or 2 M methanol at 5, 0 or −5 °C for 2, 4, 8 and 16 h. When oocytes were chilled with no cryoprotectant (CPT) or 1 M methanol at 5 or 0 °C, the mtDNA CNs initially increased at hour 2 of incubation, although it decreased significantly over the 16 h of incubation in chilled oocytes at −5 °C. The mtDNA CN increased and picked in 0.5 M methanol at 5 °C and 0 °C at hour 8 of incubation in chilled oocytes indicating that the high mtDNA CN of these oocytes is probably responsible for withstanding high chilling sensitivity. We currently propose that 0.5 M methanol is the optimal CPT for oocytes of Echinopora sp., and potentially other reef corals.